Malignant Oestrogen-producing Teratoma in a Cat. Issue 2 (February 2017) - Machida, Y.; Michishita, M.; Wada, M.; Hori, T.; Kawakami, E.; Yoshimura, H.; Ohkusu-Tsukada, K.; Taya, K.; Takahashi, K.
Summary: A 5-year-old female domestic shorthair cat was presented with abdominal distension and serum biochemical evaluation indicated a high concentration of oestradiol (32.81 pg/ml). Exploratory laparotomy revealed a large cystic mass in the right ovary with cystic fluid containing a high level of oestradiol (18.80 pg/ml). The tumour was composed of immature neuroectodermal tissue, mature cartilage, smooth muscle, adipose tissue and aggregated, poorly differentiated mesenchymal cells. It contained cysts of various sizes that were lined by epithelium of different types. The basal layer of the lining epithelium was shown to express aromatase by immunohistochemistry. The findings suggest that this was a novel, malignant, oestrogen-secreting teratoma and that the aromatase-positive, neoplastic cells may have been the source of elevated levels of serum oestrogen.